The Authority of a Notary in the Creation of Deeds in the Field of Land Affairs - Widodo Budidarmo; Lily Kalyana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The land holds significant importance for the people in Indonesia and is one of the country's natural resources. As an agricultural country, a large portion of the Indonesian population relies on agriculture as their primary source of livelihood. Farming, which involves cultivating land to produce food, has long been a cornerstone of rural economies. Notaries and Land Deed Officials (PPAT) play a critical role in Indonesia’s legal and land administration systems. Notaries, governed by Law No. 2 of 2014 and Article 1868 of the Indonesian Civil Code (KUHPerdata), are authorized to create authentic deeds, ensure legal certainty, and maintain document custody. Meanwhile, PPATs, under Government Regulation No. 37 of 1998 and Law No. 4 of 1996, are responsible for drafting deeds related to land registration and mortgage rights, including transactions involving the sale, purchase, and transfer of land rights. The distinct authority of notaries and PPATs is clearly defined by the relevant regulations, with the Constitutional Court Decision No. 5/PUU-XII/2014 affirming that their jurisdictions do not overlap, thereby safeguarding legal certainty in land administration.